2020
DOI: 10.1002/ejsp.2694
|View full text |Cite
|
Sign up to set email alerts
|

Subjective status and perceived legitimacy across countries

Abstract: The relationships between subjective status and perceived legitimacy are important for understanding the extent to which people with low status are complicit in their oppression. We use novel data from 66 samples and 30 countries ( N = 12,788) and find that people with higher status see the social system as more legitimate than those with lower status, but there is variation across people and countries. The association between subjective status and perceived legitimacy was never negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 68 publications
5
65
0
3
Order By: Relevance
“…For example, experiments have found that manipulating individuals to perceive higher levels of social mobility increases their tendency to justify the current economic system and its levels of inequality (Day and Fiske 2016). A large cross-national survey found that individuals with low status who perceived social mobility as a possibility were more likely to legitimize the system and so to accept more inequality, in line with suggestions that hope for future increases in personal status may underlie attitudes towards inequality (Brandt et al 2020).…”
Section: Self-interest and System Justificationmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, experiments have found that manipulating individuals to perceive higher levels of social mobility increases their tendency to justify the current economic system and its levels of inequality (Day and Fiske 2016). A large cross-national survey found that individuals with low status who perceived social mobility as a possibility were more likely to legitimize the system and so to accept more inequality, in line with suggestions that hope for future increases in personal status may underlie attitudes towards inequality (Brandt et al 2020).…”
Section: Self-interest and System Justificationmentioning
confidence: 95%
“…Experimental work has also found that people are more likely to justify the current system when they believe there is hope that their group's status position will improve in the future (Owuamalam et al 2016; see also Owuamalam et al 2017Owuamalam et al , 2018, in line with motives of collective self-interest rather than system justification. Indeed, a recent novel and large-scale survey across 66 samples in 30 countries found that individual status and the perceived legitimacy of the system were consistently positively associated, including among those with low status (Brandt et al 2020), against predictions derived from system justification theory.…”
Section: Self-interest and System Justificationmentioning
confidence: 97%
“…This is seen as much among the advantaged as among the disadvantaged. Indeed, the paradox underlying system justification theory relates to the fact that the disadvantaged are no less likely than the privileged to believe that social system is legitimate and good [9,11,33]. On the contrary, the motivation to justify the system is particularly strong among them.…”
Section: Introductionmentioning
confidence: 99%
“…Otros han demostrado lo contrario a esta situación, las personas con un estatus social bajo han mostrado una menor aceptación al sistema (por ejemplo, Yang et al, 2016;Zimmerman y Reyna, 2013). Brandt et al (2020) indican que "las personas con un estatus más alto ven el sistema social como más legítimo que aquellos con un estatus más bajo, pero hay variaciones entre las personas y los países" (Brandt et al, 2020, p. 923). Li et al (2020) indican que dependiendo de la objetividad o subjetividad del estatus socioeconómico más bajo de las personas se relacionan de forma diferente con la legitimidad.…”
Section: Pragmáticaunclassified